2017
DOI: 10.1063/1.4979031
|View full text |Cite|
|
Sign up to set email alerts
|

Chiral magnetoresistance in Pt/Co/Pt zigzag wires

Abstract: The Rashba effect leads to a chiral precession of the spins of moving electrons while the Dzyaloshinskii-Moriya interaction (DMI) generates preference towards a chiral profile of local spins. We predict that the exchange interaction between these two spin systems results in a 'chiral' magnetoresistance depending on the chirality of the local spin texture. We observe this magnetoresistance by measuring the domain wall (DW) resistance in a uniquely designed Pt/Co/Pt zigzag wire, and by changing the chirality of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 33 publications
(47 reference statements)
0
16
0
Order By: Relevance
“…Thus, the relatively large MR response observed in transport measurements alludes to the possibility that the spin-dependent scattering mechanism in domains and domain walls occurs. (40,(43)(44)(45)(46)(47)(48) The heterojunction structure composed of ferromagnetic and ferroelectric layers provides a crucial key to investigating the fundamental physical mechanism and producing artificial multiferroic functional materials and devices.…”
Section: ( )mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the relatively large MR response observed in transport measurements alludes to the possibility that the spin-dependent scattering mechanism in domains and domain walls occurs. (40,(43)(44)(45)(46)(47)(48) The heterojunction structure composed of ferromagnetic and ferroelectric layers provides a crucial key to investigating the fundamental physical mechanism and producing artificial multiferroic functional materials and devices.…”
Section: ( )mentioning
confidence: 99%
“…Recently, the Dzyaloshinskii-Moriya interaction (DMI) (38,39) at the interface has attracted much attention because it facilitates the stabilization of homochiral Néel domain walls. (40) Thus, a domain wall is not only a unique object but also plays a significant role in magnetization reversal and scattering properties. Here, we investigated the fundamental properties of the domains and domain walls formed in the Ni wire fabricated on the singlecrystal lithium niobate (LiNbO 3 ) Y-cut 128° substrate.…”
Section: Introductionmentioning
confidence: 99%
“…[73] Notably, the chiral derivative is a powerful tool to describe the symmetry of DMI and SOT for other types of SOC (i.e., Dresselhaus SOC and Weyl SOC), [74] which is consistent with a microscopic calculation of DMI. [75] It is also useful for describe a chirality of other physical phenomena such as the damping, [76] gyromagnetic ratio, [76] magnetoresistance, [77] and the magnon torque. [78] A qualitative understanding of the interfacial DMI based on the chiral derivative is provided as follows.…”
Section: Rashba Effects On Equilibrium Magnetic Energies In Nm/fm Bilmentioning
confidence: 99%
“…We find that such estimation agrees well with the DW resistance for the thick Ta layer films; however, a discrepancy remains for the thinner Ta layer films. Other contribution to the DW resistance, including the recently discovered chiral DW resistance 23 , may account for the discrepancy.…”
mentioning
confidence: 96%
“…Recently, it has been reported that a chiral DW resistance appears in system with large spin orbit coupling 23 . Provided a Rashba-like Hamiltonian can describe the electronic states of the heterostructure, an additional DW resistance emerges only when the magnetic configuration is a chiral Néel type.…”
mentioning
confidence: 99%